Tommaso Natalis from Ragusa (Toma Budislavić 1545–1608), between Italy, Poland and Dalmatia - Quirini-Popławska, Danuta (Balcanica Posnaniensia. Acta et studia, 2009)
The article presents the biography and activities of Tommaso Natalis of Ragusa (Toma Budislavić, 1545–1608), a Dalmatian humanist, physician, and clergyman whose life and work reflect the cultural and intellectual connections among Italy, Poland, and Dalmatia in the second half of the sixteenth century. The aim of the study is to examine Natalis’s role as an intermediary between the scientific, religious, and political milieus of Central and Southern Europe and to highlight his significance in the development of Polish–Dalmatian-Italian relations. The research is based on manuscript materials from the Bolognese Fondo Aldrovandi, diplomatic correspondence contained in the Monumenta Poloniae Vaticana, and archival documents from Rome, Kraków, and Dubrovnik. The author employs a historical and comparative method, combining biographical research with an analysis of the broader cultural and political context. The findings show that Natalis was not only an outstanding physician educated at the universities of Bologna and Padua but also a collaborator of the Holy See, active among papal nuncios and legates in Poland. In Kraków, where he served as the personal physician to Bishop Piotr Myszkowski, he played a significant role in the intellectual and publishing circles, maintaining contacts with figures such as Jan Kochanowski and Stanisław Sokołowski. His diplomatic and ecclesiastical work also included missions to Wallachia and Moldavia. The study concludes that Tommaso Natalis represents a quintessential Renaissance figure—a learned man, traveler, and cultural mediator who bridged the traditions of Italian humanism with the intellectual and religious culture of Central and Eastern Europe.